Innate immunity but not NLRP3 inflammasome activation correlates with severity of stable COPD. Issue 6 (15th January 2014) - Di Stefano, Antonino; Caramori, Gaetano; Barczyk, Adam; Vicari, Chiara; Brun, Paola; Zanini, Andrea; Cappello, Francesco; Garofano, Elvira; Padovani, Anna; Contoli, Marco; Casolari, Paolo; Durham, Andrew L; et al.
Abstract : Background: In models of COPD, environmental stressors induce innate immune responses, inflammasome activation and inflammation. However, the interaction between these responses and their role in driving pulmonary inflammation in stable COPD is unknown. Objectives: To investigate the activation of innate immunity and inflammasome pathways in the bronchial mucosa and bronchoalveolar lavage (BAL) of patients with stable COPD of different severity and control healthy smokers and non-smokers. Methods: Innate immune mediators (interleukin (IL)-6, IL-7, IL-10, IL-27, IL-37, thymic stromal lymphopoietin (TSLP), interferon γ and their receptors, STAT1 and pSTAT1) and inflammasome components (NLRP3, NALP7, caspase 1, IL-1β and its receptors, IL-18, IL-33, ST2) were measured in the bronchial mucosa using immunohistochemistry. IL-6, soluble IL-6R, sgp130, IL-7, IL-27, HMGB1, IL-33, IL-37 and soluble ST2 were measured in BAL using ELISA. Results: In bronchial biopsies IL-27+ and pSTAT1+ cells are increased in patients with severe COPD compared with control healthy smokers. IL-7+ cells are increased in patients with COPD and control smokers compared with control non-smokers. In severe stable COPD IL-7R+, IL-27R+ and TSLPR+ cells are increased in comparison with both control groups. The NALP3 inflammasome is not activated in patients with stable COPD compared with control subjects. The inflammasome inhibitory molecules NALP7 and IL-37 are increased in patients with COPD compared with control smokers. IL-6 levels are increased in BAL from patients with stable COPD compared with control smokers with normal lung function whereas IL-1β and IL-18 were similar across all groups. Conclusions: Increased expression of IL-27, IL-37 and NALP7 in the bronchial mucosa may be involved in progression of stable COPD.